2018
DOI: 10.1001/jama.2017.20121
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Red Blood Cell, Plasma, and Platelet Transfusions in the United States, 1993-2014

Abstract: Blood transfusions are one of the most common hospital procedures. Randomized trials have demonstrated the safety of restrictive transfusion strategies. 1 Hospitals have subsequently implemented patient blood management programs to facilitate restrictive transfusion practices aimed to improve patient outcomes, reduce costs, and conserve blood. We are unaware of nationally representative studies evaluating temporal trends in red blood cell (RBC), plasma, and platelet transfusions while accounting for the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 6 publications
4
67
1
Order By: Relevance
“…Blood transfusion is a lifesaving procedure that is integral to the management of many surgical and medical pathologies. In the United States (U.S.), blood transfusion rates have steadily declined over 30% in the past decade . Several factors have contributed to this decline, including the availability of revised clinical guidelines, implementation of patient blood management programs, an expanded repertoire of marrow‐sparing and hemostatic agents, and an increase in the practice of minimally invasive surgeries .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Blood transfusion is a lifesaving procedure that is integral to the management of many surgical and medical pathologies. In the United States (U.S.), blood transfusion rates have steadily declined over 30% in the past decade . Several factors have contributed to this decline, including the availability of revised clinical guidelines, implementation of patient blood management programs, an expanded repertoire of marrow‐sparing and hemostatic agents, and an increase in the practice of minimally invasive surgeries .…”
mentioning
confidence: 99%
“…Several factors have contributed to this decline, including the availability of revised clinical guidelines, implementation of patient blood management programs, an expanded repertoire of marrow‐sparing and hemostatic agents, and an increase in the practice of minimally invasive surgeries . Despite these advancements, blood transfusion remains common in U.S. hospitals …”
mentioning
confidence: 99%
“…The results demonstrated a continued downtrend of blood collections and transfusions (Table ). A study using the National Inpatient Sample also found decreases in the proportion of inpatients receiving transfusions (Table ). Several factors have contributed to this decline, including better surgical techniques, and implementation of patient blood management programs.…”
Section: Big Data Applications and Omics Studies In Transfusion Medicinementioning
confidence: 96%
“…RBC use has declined by approximately 25% to 30% in the United States, without measured adverse effects on patient outcomes and with reduced costs . During the same period, the practice of PC transfusion has changed very little: Minimum prophylactic platelet count transfusion thresholds are well defined in nonbleeding, hospitalized, thrombocytopenic hematology/oncology patients, but these account for less than one‐half of PC transfusions . Use is more variable in the outpatient and surgical settings .…”
Section: Introductionmentioning
confidence: 99%